Evaluation of Adhesion and Viability of Human Gingival Fibroblasts on Strontium-Coated Titanium Surfaces: an in vitro Study - Bakitian F; Alshammari H; Youssef AR; Hawsawi RA; Alreshedi AD; Alkhashram MA (Dove Medical Press, 2024)
Fahad Bakitian,1 Hatem Alshammari,2 Abdel-Rahman Youssef,3,4 Rayan A Hawsawi,1 Anwar Doufan Alreshedi,2 Mariam Abdulaziz Alkhashram2 1Department of Restorative Dentistry, Faculty of Dentistry, Umm Al-Qura University, Makkah, Saudi Arabia; 2Department of Preventive Dentistry, College of Dentistry, University of Hail, Hail, Saudi Arabia; 3Department of Basic and Clinical Oral Sciences, Faculty of Dentistry, Umm Al-Qura University, Makkah, Saudi Arabia; 4Department of Microbiology and Immunology, Faculty of Medicine, Suez Canal University, Ismailia, EgyptCorrespondence: Fahad Bakitian, Department of Restorative Dentistry, Faculty of Dental Medicine, Umm Al-Qura University, Makkah, Saudi Arabia, Tel +966 500507661, Email fabakitian@uqu.edu.saBackground: Applying multifunctional coatings employing strontium (Sr) ions on titanium (Ti) surfaces is a useful and biocompatible method to improve osseointegration and prevent tissue infections through antimicrobial activity. Nonetheless, the effectiveness of Sr coating on the adhesion and viability of human gingival fibroblasts (HGFs) to Ti surfaces remains unclear.Purpose: The study aimed to evaluate the effect of Sr coating on the adhesion and viability of HGFs to Ti surfaces.Materials and Methods: The Ti wafers were divided into two groups based on Sr coating: uncoated Ti (control) and Sr-coated Ti. The Magnetron sputtering technique was used for Sr coating on Ti surfaces. The HGFs were seeded onto the surfaces and cultured for 48 and 96 hours before the cell adhesion and viability of the attached HGFs were assessed. The adhesion of HGFs was analyzed using the attached cell numbers at 48 h and 96 h, and the morphology at 24 h and 72 h. The cytotoxic effect on HGFs was assessed after 24 and 72 hours of incubation using cell viability assay. Student's t-test was used for statistical analysis.Results: The number of cells attached to Sr-coated surfaces was significantly greater than those attached to uncoated Ti surfaces after 48 hours (P< 0.0001) and 96 hours (P=0.0002). Sr-coated and uncoated Ti surfaces were not cytotoxic to HGFs, with the cell viability ranging from 92% to 105% of the untreated control HGFs. There were no significant differences in cell viability between Sr-coated and uncoated Ti surfaces at 24 hours (P=0.3675) and 72 hours (P=0.0982).Conclusion: Sr-coated Ti surfaces induce adhesion of HGFs compared to uncoated Ti surfaces. Further, Sr-coated and uncoated Ti surfaces show no cytotoxic effect on the attached HGFs.Keywords: cytotoxicity, dental implant, peri-implantitis, metal ions, multifunctional coatings, titanium surfaces